African Post-Slavery: A History of the Future - Rossi, Benedetta (The International journal of African historical studies, 2015)
Here some normative interpretations are incompatible with international treaties and conventions of which these countries are co-signatories.5 Ann Mayer has shown that from an Islamic perspective equal rights for women and foreigners are the most controversial aspects of international human rights law.6 Annie Bunting has explored the local interpretations of Islamic and international law in relation to early marriage in Northern Nigeria, where international human rights are contested by men and women alike. 7 Different Muslim constituencies give different interpretations of Islamic Law with regard to the circumstances of slave descendants and their legal position vis-à-vis the descendants of their former owners.8 Abdel Wedoud Ould Cheikh has shown that in Mauritania the legal status of slave descendants, their rights and obligations toward former masters, and their claims to the ownership of land are deeply contested.9 Not only are Islamic perspectives sometimes in conflict with international antislavery legislation, but there is no unified Islamic position with regard to contemporary slavery.10 Legal, normative, and religious pluralism belong to the longue durée of African history and influence the reception of international anti-slavery law. [...]the English word "slave" fails to convey the nuances expressed in vernacular names that distinguish across distinct categories of slaves and slave descendants.66 The use of vernacular terminology is not always a satisfactory solution, because the living conditions of the descendants of those who occupied these statuses have been changing: